AFM studies of polypyrrole film surface morphology - II. Roughness characterization by the fractal dimension analysis - Silk, T; Hong, Q; Tamm, J; Compton, R (1998)
The fractal dimension of electrogenerated polypyrrole films with chloride, sulfate, perchlorate and dodecylsulfate (DDS) anions as dopants is investigated by using atomic force microscopy under ex situ conditions. The results for films both as-prepared and after potentiodynamic cycling in various supporting electrolytes is presented and discussed. © 1998 Elsevier Science S.A.